Viuron (self security product) / Mohd Ikmal Hakim Bakri - Hakim Bakri, Mohd Ikmal (Universiti Teknologi MARA, Kedah, 2018)
In this decade, Tourism is one of largest, dynamic and attractive for economic development specifically in the developing countries. In Malaysia, tourism sector emerged in the 1960s as one of the new forces for economic development but the growth was slow. But today, tourism industries become as one of the main contributor to Malaysia's incomes. Furthermore, safety and security concerns in the tourism industry are critical aspects that need to be seriously considered to ensure that tourist destinations remain as a safe place of choice among the tourists. Malaysia has recorded among the firs rank of 8 countries in 2017 crime and safety index in South Asia. Tourism industry is very important in Malaysia as the largest source of income. So, the safety factor of tourist in Malaysia is important and must be highlighted by the Malaysia government. Nowadays, there are many of safety and security tools that are produce for people to protect themself from crime. since studies has shown that tourist do not carry self-defense tools while travelling, this product is introduced to solve the issue of security and crime on travelling.